2013
DOI: 10.1155/2013/537160
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Parent Satisfaction with a Dietitian-and Nurse-Led Celiac Disease Clinic for Children at the Stollery Children’S Hospital, Edmonton, Alberta

Abstract: Results of the present survey suggested that patients and families value a multidisciplinary follow-up clinic for children with celiac disease. In particular, feedback based on repeat blood work and regular contact with a dietitian were highly valued. The present survey, outlining the most valued aspects of the clinic, may be useful for service delivery in other regions. In addition, it provides information on how to better support pediatric patients with celiac disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 17 publications
(15 reference statements)
1
20
0
Order By: Relevance
“…The QoL tool used was largely descriptive; therefore, study conclusions regarding the QoL factors influencing dietary intake are limited. Finally, it is challenging to identify a comprehensive tool to evaluate overall diet quality in children and adolescents on the GFD [31,32]. Although HEI-C and the comparison of intake by food group provide insight into dietary quality, they do not address the complex factors (e.g., behavioural, psychosocial) that are important to meal patterning (i.e., meal timing, size of food portions) or specifically address micronutrient intake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The QoL tool used was largely descriptive; therefore, study conclusions regarding the QoL factors influencing dietary intake are limited. Finally, it is challenging to identify a comprehensive tool to evaluate overall diet quality in children and adolescents on the GFD [31,32]. Although HEI-C and the comparison of intake by food group provide insight into dietary quality, they do not address the complex factors (e.g., behavioural, psychosocial) that are important to meal patterning (i.e., meal timing, size of food portions) or specifically address micronutrient intake.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that children with CD receive in-depth nutritional education and report high satisfaction with dietetic services within our clinics, significant issues related to nutritional adequacy of the GFD in children and adolescents with CD remain [32]. Challenges related to food cost and availability of nutrient dense-GF foods that meet the needs of ethnically diverse populations are factors likely to influence the quality of nutrient intake in children and adolescents with CD on the GFD.…”
Section: Relevance To Practicementioning
confidence: 99%
“…Previous research has largely utilised a Likert-scale-style and closed questions to capture patient preferences in dietetic services. These studies have determined similar key indicators, such as interdisciplinary collaboration (24) , interpersonal communication skills (25)(26)(27) , empathy (28) and patient involvement (30) . A strength of the present study is the use of more open-ended questions and triangulation through indepth qualitative interviews.…”
Section: Discussionmentioning
confidence: 99%
“…After diagnosis is made, however, the follow-up is made in most cases by a specialized Celiac Center in which the CD awareness is assured. Follow-up should include a dietitian consultation, as patients report better satisfaction when they are referred to dieticians [ 21 , 22 ] and psychological support when required [ 23 ]. The importance of a psychological support has been recently reported by Sainsbury et al [ 24 ] who found that psychological symptoms and the GFD adherence were more strongly related to reduce QoL than gastrointestinal symptoms.…”
Section: Awareness Of the Disease Among Caregiversmentioning
confidence: 99%